Traditions of “Alexandria” in Prose of 20th Century: from Stylization to Parody - O. I. Osipova; O. A. Sysoyeva (Научный диалог, 2019)
The problem of modelling a classical plot in the literature of modernism and postmodernism is considered. Attention is paid to the transformation of the story of Alexander the Great in the novels of Mikhail Kuzmin (1872-1936) and Sasha Sokolov (b. 1943). The results of comparative analysis of two novels of different literary directions are presented. The question is raised that the classic story and image are transformed, becoming a way of artistic understanding of the worldview of the era. Particular attention is paid to the methods of stylization and parody in the studied texts. It is shown that the authors in the classic examples are looking for the ways to resolve the conflicts of our time: M. Kuzmin’s application to the image of the great commander is an artistic interpretation of the tragedy of human existence that have reached a lot in this world, but can not change the fate; Sasha Sokolov writes his “Palisandria” to depict the new ironic perspective on the historical process. The relevance of the study is due to the need of modern literary studies in typological studies, in the search for intertextual links. The novelty of the study is seen in the fact that the comparison of plot and figuratively close texts in the main literary directions of the 20th century allows to see ways of modelling a classic plot in its variants, taking into account the specifics of modernism and postmodernism.